Arid vegetables for farmers’ prosperity - Verma, A K; Choudhary, B R; Samadia, D K (Indian Horticulture, 2019)
As the population is increasing and agricultural land is decreasing day-byday due to urbanization and industrialization, meeting food requirement will be very difficult with the present scenario. Providing food security alone is not sufficient in developing countries like India where malnutrition is a major challenge, nutritional security becomes very important which can be achieved through the diversified and highly nutritive vegetables. Thus, the only option available to mitigate this challenge is to either increase the productivity of the existing crop or bring non-traditional areas under cultivation which can be made more productive by providing adequate technologies. Climate and soil conditions of arid region are conducive to grow different vegetables in different seasons of the year. Besides, adoption of improved varieties developed by the institute offers great potential not only for farmers prosperity through more income per unit area but for nutritional security as well.